ANALYZING THE ABILITY OF USING ADVERBS IN WRITING DESCRIPTIVE TEXT: Using adverbs in writing Descriptive Text - Tafuli, Agri Yublina; Wisrance, Maria Wihelmina; Sahan, Anselmus (Jurnal Edulanguage: Jurnal Pendidikan Bahasa, 2024)
The research was conducted at SMPN Tublopo, involving eighth grade students. Applying a qualitative method, the study focused on assessing the students' proficiency in utilizing adverbs in descriptive writing. Additionally, it sought to identify the challenges they faced in using adverbs in their compositions. The research employed written tests and interviews as data collection tools. The findings revealed that the students achieved an average score of 80, indicating an excellent level of performance. The result of the interview revealed that majority of students possess a comprehension of adverbs related to time and place, whereas they struggle with the usage of other types of adverbs. This challenge arose due to their difficulty in distinguishing between these different categories of adverbs. Keywords: Ability, Adverbs, Analyzing, Descriptive Text, Writing